المسؤولية الإدارية للم ا رفق الإستشفائية العمومية في القانون الج ا زئر ي مذكرة - الغول, هناء; الوافي, رندة (University of Eloued جامعة الوادي, 2022)
Public hospital health facilities in Algeria are of an administrative nature, enjoying legal personality and financial independence, which aims to preserve public health and meet the needs of individuals for medical and treatment services. However, these facilities have a responsibility approved by the legislator through their breach of their obligations, as this responsibility is based on the work of their employees in the hospital facility in accordance with the general rules on the basis of error, This is to have an error on the part of the administration and damage and a causal relationship between the activity of the facility and the damage that befalls others, but the latter is based in the absence of error, and this is on the basis of the risks, through which the patient is exempted from proving the error of the medical facility. If the responsibility of the medical facility finds its merits, whether it is based on fault or without fault, the burden of the obligation falls on this facility to compensate the damages incurred by the aggrieved from medical or treatment errors، Compensation is the main goal that the injured person seeks to achieve in order to compensate for the damage he has suffered.تعتبر الم ا رفق الصحية الإستشفائية العمومية في الج ا زئر، ذات طابع إداري تتمتع بالشخصية المعنوية و الإستقلال المالي، التي تهدف إلى الحفاظ على الصحة العامة و تلبية حاجيات الاف ا رد من خدمات طبية و علاجية. إلا أن لهذه الم ا رفق مسؤولية أقرها المشرع من خلال إخلالها بإلتزماتها، حيث تقوم هذه المسؤولية عن أعمال موظفيها بالمرفق الإستشفائي طبقا للقواعد العامة على أساس الخطأ، و ذلك أن تتوفر على خطأ من جهة الإدارة و ضرر و علاقة سببية بين نشاط المرفق والضرر الذي أصاب الغير، إلا أن هذه الأخيرة تقوم في غياب الخطأ، وهذا على أساس المخاطر، التي يعفى من خلالها المريض من إثبات خطأ المرفق الطبي. فإذا ما توافر لمسئولية المرفق الطبي موجبات قيامها سواء كانت قائمة على أساس الخطأ أو دون خطأ وقع على عاتق هذا المرفق عبء الالت ا زم بتعويض الأض ا رر التي لحقت بالمضرور من أخطاء طبية أو مخاطر، فالتعويض هو الغاية الأساسية التي يسعى المضرور لتحقيقها لجبر ما أصابه من ضرر.
مذكرة ماستر
Keywords: liability based on risk, liability without fault, medical errors, risks.; مسؤولية على أساس الخطأ، مسؤولية دون خطأ، أخطاء طبية، مخاطر.